Dynamic Multimatrix Laboratory Biochemical Profiling of Pulmonary Surfactant Replacement Therapy in Preterm Infants with Neonatal Respiratory Distress Syndrome: A Retrospective Cohort Study - Chen, Huifen; Bai, Xingyu; Bai, Xingyu; Wei, Dawei; Zheng, Shuang; Zhang, Mengbin; Qiao, Yanxia (Journal of Medical Biochemistry, 2026)
Background: Neonatal respiratory distress syndrome (NRDS) remains one of the major causes of early death and long-term multiorgan injury in preterm infants. Although exogenous pulmonary surfactant (PS) replacement therapy has reduced acute mortality, the incidences of bronchopulmonary dysplasia and intracranial hemorrhage remain high, and the biochemical basis underlying these residual complications has not been fully defined. This study aimed to investigate the regulatory effects of PS replacement therapy on the multiorgan biochemical status of preterm infants with NRDS.Methods: A total of 99 preterm infants with NRDS admitted to our hospital from January 1 to December 31, 2025 were included and divided into the PS treatment group (n=47) and the control group (n=52) according to treatment strategy. More than 50 markers involving nine core biochemical pathways were measured in serum, cerebrospinal fluid, and bronchoalveolar lavage fluid before treatment, 72 h after treatment, and 7 d after treatment. These markers covered bronchial development, intracranial injury, oxidative stress, inflammatory response, coagulation-fibrinolysis, vascular endothelial function, energy metabolism, and hepatic function.Results: Before treatment, no significant differences were found in any biochemical indicators between the two groups (P>0.05). At 72 h and 7 d after treatment, the levels of markers related to bronchial epithelial injury, intracranial injury, oxidative injury, inflammatory response, coagulation-fibrinolytic disorder, and vascular endothelial injury were lower in the PS treatment group than in the control group (P